Cerebral Autoregulation Monitoring with Ultrasound-Tagged Near-Infrared Spectroscopy in Cardiac Surgery Patients. (November 2015) - Hori, Daijiro; Hogue, Charles W.; Shah, Ashish; Brown, Charles; Neufeld, Karin J.; Conte, John V.; Price, Joel; Sciortino, Christopher; Max, Laura; Laflam, Andrew; Adachi, Hideo; Cameron, Duke E.; et al.
Abstract : BACKGROUND: Individualizing mean arterial blood pressure (MAP) based on cerebral blood flow (CBF) autoregulation monitoring during cardiopulmonary bypass (CPB) holds promise as a strategy to optimize organ perfusion. The purpose of this study was to evaluate the accuracy of cerebral autoregulation monitoring using microcirculatory flow measured with innovative ultrasound-tagged near-infrared spectroscopy (UT-NIRS) noninvasive technology compared with transcranial Doppler (TCD). METHODS: Sixty-four patients undergoing CPB were monitored with TCD and UT-NIRS (CerOx™). The mean velocity index (Mx) was calculated as a moving, linear correlation coefficient between slow waves of TCD-measured CBF velocity and MAP. The cerebral flow velocity index (CFVx) was calculated as a similar coefficient between slow waves of cerebral flow index measured using UT-NIRS and MAP. When MAP is outside the autoregulation range, Mx is progressively more positive. Optimal blood pressure was defined as the MAP with the lowest Mx and CFVx. The right- and left-sided optimal MAP values were averaged to define the individual optimal MAP and were the variables used for analysis. RESULTS: The Mx for the left side was 0.31 ± 0.17 and for the right side was 0.32 ± 0.17. The mean CFVx for the left side was 0.33 ± 0.19 and for the right side was 0.35 ± 0.19. Time-averaged Mx and CFVx during CPB had a statistically significant "among-subject" correlation ( r = 0.39; 95% confidence interval [CI], 0.22–0.53; P < 0.001) but had only a modest agreement within subjects (bias 0.03 ± 0.20; 95% prediction interval for the difference between Mx and CFVx, −0.37 to 0.42). The MAP with the lowest Mx and CFVx ("optimal blood pressure") was correlated ( r = 0.71; 95% CI, 0.56–0.81; P < 0.0001) and was in modest within-subject agreement (bias −2.85 ± 8.54; 95% limits of agreement for MAP predicted by Mx and CFVx, −19.60 to 13.89). Coherence between ipsilateral middle CBF velocity and cerebral flow index values averaged 0.61 ± 0.07 (95% CI, 0.59–0.63). CONCLUSIONS: There was a statistically significant correlation and agreement between CBF autoregulation monitored by CerOx compared with TCD-based Mx. Abstract : Published ahead of print September 2, 2015